2016
DOI: 10.1158/1078-0432.ccr-15-1295
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Dosing for Targeted Therapies in Oncology: Drug Development Cases Leading by Example

Abstract: One of the key objectives of oncology first-in-human trials has often been to establish the maximum tolerated dose (MTD). However, targeted therapies might not exhibit doselimiting toxicities (DLT) at doses significantly higher than sufficiently active doses, and there is frequently a limited ability to objectively quantify adverse events. Thus, while MTD-based determination of recommended phase II dose may have yielded appropriate dosing for some cytotoxics, targeted therapeutics (including monoclonal antibod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 32 publications
0
109
0
Order By: Relevance
“…However, tolerability is essential for adherence to therapy especially if long‐term administration is anticipated. Recently, dosing selection based on exposure‐response relationship considering both efficacy and tolerability has drawn attention by both regulatory agency and industry in oncology drug development 30, 31. The purpose of this research was to select the sorafenib dosing regimen in patients with AML for further clinical trials by characterizing the exposure‐response relationship for inhibition of FLT3 by sorafenib and its active N‐oxide metabolite in patients with AML.…”
mentioning
confidence: 99%
“…However, tolerability is essential for adherence to therapy especially if long‐term administration is anticipated. Recently, dosing selection based on exposure‐response relationship considering both efficacy and tolerability has drawn attention by both regulatory agency and industry in oncology drug development 30, 31. The purpose of this research was to select the sorafenib dosing regimen in patients with AML for further clinical trials by characterizing the exposure‐response relationship for inhibition of FLT3 by sorafenib and its active N‐oxide metabolite in patients with AML.…”
mentioning
confidence: 99%
“…However, many selective targeted agents may not reach MTD (36,37), or such doses may be significantly higher than those required for the optimal target suppression (36,38), also known as a BED. A recent review of cancer drug monotherapies found that >60% of approved drugs have doses lower than the MTD (36). For targeted therapies such as highly selective TKIs or monoclonal antibodies, BED provides a safe and effective alternative strategy.…”
Section: Identify Biologically Effective Doses (Beds) For Highly Selementioning
confidence: 99%
“…For solid tumors, the RECIST classification of tumor measurement is the most commonly employed to define response and progression; however, this classification uses a binary system (response vs. no response) in assessing an exposure-response relationship. The proposal to use a measurement of change in tumor size, which is a continuous data element, may provide more information in an exposure-response relationship and ultimately require fewer patients in a randomized, phase II, dose-comparison trial, thus increasing efficiency in the dose-finding endeavor (12,13). This approach may be more difficult in phase I trials in which patients frequently are heavily pretreated, and overall response rates typically are low.…”
Section: Design Of Dose-finding Trialsmentioning
confidence: 99%